The impact of fiscal deficits on capital flows in an ‘at-risk’ framework across both resident and non-resident flows in South Africa - Meerholz, Yasmin (University of the Witwatersrand, Johannesburg, 2023)
This paper studies the determinants of capital flows to South Africa by using the ‘at-risk’ framework developed by Adrian et al. (2019) and adapted for capital flow analysis in the seminal paper of Gelos et al. (2022). It extends the work of Goel and Miyajima (2021) on South Africa by including fiscal deficits as an independent variable to analyse the response of resident and non-resident flows to increases in fiscal deficits. The approach uses quantile regression to predict the probability distributions of capital flows to South Africa conditional on domestic economic and financial conditions, and external risk sentiment. Focusing on the tails as opposed to the median of the capital flow probability distributions allows for the examination of extreme cases of capital flows, such as sudden stops and surges. This paper finds a generally strong buffer effect of resident capital flows against non-resident outflows, except in the case of global risk aversion. Domestic fiscal deficits are found to have an impact on both resident and non-resident capital flows, with a specifically strong response of non-resident FDI to domestic fiscal deficits. This highlights the risk of non-resident capital flight in response to increasing fiscal deficits, and the need to properly manage fiscal deficits. This paper has important policy implications as it allows for a better understanding of what causes and subsequently what should help mitigate extreme capital flows
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Capital flows; Fiscal deficit; At-risk framework; NON-RESIDENT FLOWS; UCTD; SDG-8: Decent work and economic growth